Bridging trade, finance, and the environment: the mediating role of growth in the belt and road countries - Khan, Abrar; Gang, Tian; Ullah, Ikram; Deka, Abraham; Mingye, Tang (Frontiers in Environmental Science, 2026)
Recent empirical research investigates the relationship between economic growth and environmental quality, focusing on global trade, foreign direct investment, financial development, and energy consumption. However, much of the existing literature does not distinguish between the direct and indirect effects of these macroeconomic variables on environmental quality. Therefore, this study uses economic growth as a mediating variable to separate the direct and indirect impacts of foreign direct investment, financial development, trade, and renewable energy consumption on environmental outcomes. Using a panel dataset of 26 Belt and Road Initiative countries from 1995 to 2020, the research estimates three econometric models employing the Feasible Generalized Least Squares method with Panel-Corrected Standard Errors to obtain robust estimates despite heteroskedasticity and cross-sectional dependence. The results reveal significant changes in both the signs and magnitudes of the estimated coefficients when economic growth is included as a mediating factor. Notably, the direct impact of trade becomes negative, while the effects of foreign direct investment and financial development diminish, suggesting that their environmental influence is transmitted mainly through economic growth. In contrast, the impact of renewable energy consumption remains unchanged. These findings emphasize the importance of accounting for economic activity in understanding how macroeconomic variables affect the environment. These findings further underline the need for policies that support low carbon technologies within trade and investment frameworks, and promote financial instruments that support sustainable growth to ensure that economic expansion does not cause CO2 emissions.